Effect of vam and phosphorus on yield and quality of sunflower: Effect of vam and phosphorus on yield and quality of sunflower - C KALAIYARASAN; R.RAMESH; S JAWAHAR; M V SRIRAMACHANDRASEKHARAN; K SUSEENDREN (Journal of Oilseeds Research, 2023)
The field experiment was conducted at Experimental Farm, Department of Agronomy, Annamalai University, Tamil Nadu during July – October 2015 to study the effect of mycorrhizal inoculation (VAM) and different levels of phosphorus on yield and quality of hybrid sunflower cv. Sunbred.The experiment was conducted in factorial randomized block design with two replications. The treatments consisted of 5 levels of P2O5 (0, 25, 50, 75 and 100kg/ha) applied in the presence or absence of VAM inoculates. The results of experiment revealed that mycorhizal inoculated plants produced maximum seed and stalk yield, oil content, oil yield and protein content than non mycorhizal inoculation. Among the various phosphorus levels tried, P2O5 at 100 kg/ha recorded the maximum values for yield and quality. With regard to interaction effect, mycorrhizal inoculation with P2O5 @ 100 kg /ha recorded maximum values for yield and quality of sunflower but it was on par with mycorrhizal inoculation with P2O5 @ 75 kg /ha. Lowest values of yield and quality were recorded in non- mycorrhizal inoculation with P2O5 @ 0 kg /ha.